PENAMBAHAN TEPUNG BIJI CEMPEDAK DALAM PEMBUATAN ROTI TAWAR - Bangga Andreas Putra Berutu; Dewi Fortuna Ayu (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to obtain the best ratio of wheat flour and cempedak seed flour to produce a good quality white bread. This research was carried out experimentally by using completely randomized design with four treatments and four replications in order to obtain sixteen experiments unit : TC0 (100% wheat flour), TC1 (90% wheat flour and 10% cempedak seed flour), TC2 (85% wheat flour and 15% cempedak seed flour), TC3 (80% wheat flour and 20% cempedak seed flour). Analysis of variance showed that the ratio of cempedak seed flour and wheat flour adding significantly effected on moisture content, ash content, protein content, bread improver, and hedonic sensory. The best treatment of white bread according to chemical analysis and sensory assessment was TC1 (90% wheat flour and 10% cempedak seed flour) treatment which has moisture content 26,60%, ash content 1,64%, protein content 10,27%, and bread improver 252,50%. Keywords: Cempedak seed flour, wheat flour, white bread